Comportamento reprodutivo de Phyllomedusa rohdei Mertens, 1926 (Amphibia, Anura, Hylidae), na região de Saquarema, Estado do Rio de Janeiro, Sudeste do Brasil - Wogel, Henrique (2001)
The breedind activity of Phyllomedusa rohdei was observed in a temporary pond, located at Saquarema, Rio de Janeiro State, Brazil from July, 1999 to July, 2000. The reproductive period extended from December to February (wet season). Females were larger and heavier than males. Males spent relatively few nights in activity call in the chorus, with respect to the length of the breeding season. The number of males and females present in the pond was positively correlated, but no correlation was revealed between the number of males and the operational sex ratio. Larger males predominated in the chorus when there was water in the pond, while smaller males predominated when the pond was dry. The matings were non-random in relation to the following variables measured on males: snout-vent length, initial and final mass, number of nights present in the chorus and the period of permanence in the pond in December. The spatial distribution of males in the pond was clustered, the meeting occurring preferentially in places with oviposition sites. During the courtship behavior, males call and patrol the area in search of females. Females did not choose mates and the sexual selection results from male-male competition.